2008
DOI: 10.1016/j.cplett.2008.04.105
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of semiconducting behavior of carbon nanotubes using ball milling

Abstract: This paper proposes a novel chemo-mechanical method to in-situ functionalize carbon nanotubes (CNTs). Ball milling in the presence of ammonium bicarbonate allowed the introduction of amine and amide groups onto the surface of CNTs, resulting in the conversion of the semiconducting behavior of CNTs from p-type to n-type. The corresponding electrical conductivity of CNT increased gradually with ball milling time, presenting a remarkable 250% increase after 9 hrs of milling. These interesting observations are att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 26 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…This result is consistent with earlier findings. Ma et al used the ball‐milling method to introduce functional groups, such as amines and amides, to the surface of CNTs, and the semiconducting behavior of the CNTs was converted . Shao et al observed the strong interfacial interactions between PA6 and CNTs and PA6 grafting onto CNTs after pan‐milling .…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistent with earlier findings. Ma et al used the ball‐milling method to introduce functional groups, such as amines and amides, to the surface of CNTs, and the semiconducting behavior of the CNTs was converted . Shao et al observed the strong interfacial interactions between PA6 and CNTs and PA6 grafting onto CNTs after pan‐milling .…”
Section: Resultsmentioning
confidence: 99%
“…have proposed a chemomechanical method for the insitu functionalization of nanotubes in presence of ammonium bicarbonate to introduce amine and amide groups. They have also observed that the conversion of semiconducting behaviour of tubes takes place from p-type to n-type [84]. Konya et.al.…”
Section: Modification Through Ball Millingmentioning
confidence: 89%
“…Material is grinded to fine powder due to internal cascading effect of balls (ceramic, flint pebbles and stainless steel). Ball milling is successfully applied for conversion of CNTs into nanoparticle, curved or closed shell carbon nanoparticles produced from graphite, for the morphological modification of cup-stacked CNTs [86,87]. Ball milling of CNTs not only improves dispersion but can also add some functional groups on the CNT surface.…”
Section: Ball Millingmentioning
confidence: 99%